Police and the liberal state - Dubber, Markus Dirk.; Valverde, Mariana, 1955- (Stanford, Calif. : Stanford General, 2008)
This text advances a broad interdisciplinary and international project to refocus attention on the scope and function of modern government through the lens of police power in both its multiple manifestations and techniques.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Police power; Police; Criminal law; Police power -- United States; Police -- United States; Criminal law -- United States; True Crime; Social services & welfare, criminology